2021
DOI: 10.1055/a-1392-0938
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome and Fibrocystic Breast Disease: An Updated Review

Abstract: Polycystic ovary syndrome (PCOS) is the most common hormonal disorder in women of reproductive age. There is no clear association between PCOS and benign breast disease (BBD). The latter is a frequent benign disorder, affecting women between 20 and 50 years of age. To date, the classification remains controversial, and the risk of developing breast cancer that is associated with these changes is different depending on the histopathological findings. The most frequent changes are breast cysts, which are noted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Various mechanisms have been proposed for the effect of hypothyroidism on breast cells. One mechanism is that low levels of thyroid hormones in the body suppress negative self-regulation of the pituitary-hypothalamic axis, resulting in increased secretion of prolactin-like thyroid-stimulating hormone (TSH) which can affect breast cells and cause changes in breast parenchyma [ 14 , 20 , 21 , 35 ]. The next mechanism suggests that lower than normal levels of thyroid hormones may abnormally increase the sensitivity of breast epithelial cells to the stimulatory effect of prolactin [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various mechanisms have been proposed for the effect of hypothyroidism on breast cells. One mechanism is that low levels of thyroid hormones in the body suppress negative self-regulation of the pituitary-hypothalamic axis, resulting in increased secretion of prolactin-like thyroid-stimulating hormone (TSH) which can affect breast cells and cause changes in breast parenchyma [ 14 , 20 , 21 , 35 ]. The next mechanism suggests that lower than normal levels of thyroid hormones may abnormally increase the sensitivity of breast epithelial cells to the stimulatory effect of prolactin [ 36 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrocystic breast changes are the most common benign breast changes, found in 50% of women undergoing clinical examination and 90% of women undergoing histopathological examination. Fibrocystic breast changes are common in women aged 20 to 50 years [ 14 , 15 ] and their symptoms such as nipple pain and discharge can adversely affect the life quality of premenopausal women. In some previous reports, the significant association between fibrocystic breast changes and PCOS has been reported while in some others, no association has been established [ 16 – 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, based on a study, it was observed that there was no relationship between polycystic ovary syndrome frequency and breast cancer. This may be due to the age of breast cancer patients in this study, who were mostly over 40 years old (63). Wen et al (47) also investigated the causal relationship between genetically predisposed PCOS and breast cancer risk and concluded that polycystic ovary syndrome is probably a causative factor in the development of ER-positive breast cancer, which provides a better understanding of the cause of breast cancer and prevention BRCA1/2, TP53, PIK3CA, and KRAS.…”
Section: Common Genes Involved In Ovarian Cancer Breast and Polycysti...mentioning
confidence: 78%
“…D’Amelio et al showed a significant association between PCOS and benign breast pathologies 28 . In another study, they suggested that there was no significant association between benign breast pathologies and PCOS 29 .…”
Section: Discussionmentioning
confidence: 97%